Effects of Carboxymethyl Cellulose as a Surface Sizing Agent on the Printable Properties of Newspaper - (:unkn) unknown (ASIAN JOURNAL OF CHEMISTRY, 2010)
The objective of the study is to determine effects of carboxymethyl cellulose as a surface sizing agent on the printable properties of sized newspaper. In this study, the commercial newspapers were sized by K-control coater with using various concentrated carboxymethyl cellulose solutions. Sized newspapers were used for the offset print tests, which were made by IGT Cl test print machine. One property of carboxymethyl cellulose is its ability to improve the surface properties of paper when it is applied to the surface. As a result, it has been found that carboxymethyl cellulose can improve the printable properties of newspaper.
Keywords: Surface sizing; Printability; Newspaper; Offset printing; Printing ink; COATINGS; KAOLIN; CMC